Cytochemical profile of B and T leukaemic lymphocytes with special reference to acute lymphoblastic leukaemia. Issue 10 (October 1974) - Catovsky, D.; Galetto, J.; Okos, A.; Miliani, E.; Galton, D. A. G.
Abstract : The PAS and acid phosphatase reactions showed a different pattern of positivity in the cells of lymphoproliferative disorders according to their B or T cell nature. In B-cell leukaemias (chronic lymphocytic and prolymphocytic) a low proportion of lymphocytes gave a positive result with the acid phosphatase reaction, while the majority were PAS positive in granular form. In contrast, in the T-prolymphocytic and T-lymphoblastic leukaemias the acid phosphatase reaction was positive in the majority of cells, while the PAS reaction was only positive in a minority. The significance of these findings, particularly for the recognition of a distinct T-cell variant of acute lymphoblastic leukaemia, is discussed.